From record performance to hypoxia tolerance: respiratory transition in damselfish larvae settling on a coral reef - Nilsson, Göran E (The Royal Society, 2006)
The fastest swimming fishes in relation to size are found among coral reef fish larvae on their way to settle on reefs. By testing two damselfishes, Chromis atripectoralis and Pomacentrus amboinensis, we show that the high swimming speeds of the pre-settlement larvae are accompanied by the highest rates of oxygen uptake ever recorded in ectothermic vertebrates. As expected, these high rates of oxygen uptake occur at the cost of poor hypoxia tolerance. However, hypoxia tolerance is needed when coral reef fishes seek nocturnal shelter from predators within coral colonies, which can become severely hypoxic microhabitats at night. When the larvae settle on the reef, we found that they go through a striking respiratory transformation, i.e. the capacity for rapid oxygen uptake falls, while the ability for high-affinity oxygen uptake at low oxygen levels is increased. This transition to hypoxia tolerance is needed when they settle on the reef; this was strengthened by our finding that small resident larvae of Acanthochromis polyacanthus, a damselfish lacking a planktonic larval stage, do not display such a transition, being well adapted to hypoxia and showing relatively low maximum rates of oxygen uptake that change little with age.